2021
DOI: 10.1186/s13034-021-00379-1
|View full text |Cite
|
Sign up to set email alerts
|

Using the biopsychosocial model for identifying subgroups of detained juveniles at different risk of re-offending in practice: a latent class regression analysis approach

Abstract: Background Juvenile delinquents constitute a heterogeneous group, which complicates decision-making based on risk assessment. Various psychosocial factors have been used to define clinically relevant subgroups of juvenile offenders, while neurobiological variables have not yet been integrated in this context. Moreover, translation of neurobiological group differences to individual risk assessment has proven difficult. We aimed to identify clinically relevant subgroups associated with differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Future studies may focus on relating these mechanisms to (preventive) interventions (e.g. see de Ruigh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may focus on relating these mechanisms to (preventive) interventions (e.g. see de Ruigh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in the behavioral, health and social sciences are increasingly interested in investigating how the causal effect of a treatment on an outcome differs among individuals in qualitatively different latent subgroups; see e.g., [1,2,3,4,5,6,7,8,9,10]. For example, the effect of a medical intervention, such as right heart catheterization, on the six-month mortality of critically ill patients [11] may differ across patients with different latent risk profiles that depend on their medical and health status.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is of main importance to integrate neurobiological assessments with the mainly psychosocial diagnostic assessments that are currently used in clinical practice. Our previous work has shown that such a biopsychosocial approach including various neurobiological, psychological, and environmental factors in concert, can be used in defining more homogeneous clinical subsamples, in this case with different risks of criminal reoffending (de Ruigh et al., 2021). Through integrating structural biological assessments in clinical practice, data will become available that can be used to create individual diagnostic profiles in which both biological and environmental assessments are weighed.…”
mentioning
confidence: 99%